Levels of Management Commitment: A Moderator the Structural Relationships among Critical Success Factors of TQM, World-Class Performance in Operations, and Company Financial Performance - Wakhid Slamet Ciptono (Asian Journal of Technology Management, 2012)
This study investigates the moderating impacts of the three levels of management commitment (top, middle, and low levels) on the structural relationships among the constructs— six critical success factors of TQM (quality improvement program, supervisory leadership, supplier involvement, management commitment, training to improve products/services, cross-functional relationships); world-class performance in operations (world-class company practices, operational excellence practices, company non-financial performance); and company financial performance. It uses a sample of 1,332 managers in 140 strategic business units (SBUs) within 49 oil and gas companies in Indonesia. The empirical results indicate that the goodness-of-fit of the unconstrained model is much better than that of the constrained model, and this is an indicative that the three level of management moderates the structural relationships among the constructs. Those are, three levels of management act as a moderator variable between critical success factors of TQM, world-class company practices, operational excellence practices, company non-financial performance, and company financial performance. Results further reveal that world-class performances in operations (world-class company practices, operational excellence practices, and company non-financial performance) were positively mediated the impact of critical success factors of TQM on company financial performance. Results also point out that five of six critical success factors of TQM positively associated with world-class company practices and operational excellence practices under the three levels of management (top, middle, low). World-class company practices and operational excellence practices have direct and significant effects on company non-financial performance (productivity, operational reliability). Furthermore, empirical results suggest that there is a positive and significant relationship between company non-financial performance and company financial performance. Implications, limitation and lines of future research are discussed. Keywords: Company financial performance, critical success factors of TQM, world-class company practices